Management of Specialization Program on Junior High School in Madrasah Tsanawiyah Negeri (Educational Management, 2022)
The purpose of this study is to describe and analyze the planning, organizing, mobilization, controlling of the specialization program in MTs Negeri 1 Pemalang. This research approach is a qualitative approach (qualitative research) with a case study design. Data acquisition is carried out by means of interviews, observations and documentation. The results of this study show that drawn (1) Planning of the specialization superior class program is carried out by conducting strategic analysis. (2) Organizing a specialization superior class program, namely by forming a special organizational structure. (3) The mobilization or implementation of the specialization superior class program is carried out by selecting inputs, namely prospective new students through the New Student Admissions (PPDB) system, then accompanied by the process of processing these inputs. (4) Control of the specialization superior class program shall be carried out using the attendance list as a source of information related to the implementation of the superior class program. The filling of the attendance list in each meeting session in the classroom is filled in both by the teacher / tutor and by the student.